Formation of diphosphorus (P2+) and phosphorus mononitride (PN+) cations by radiative association - Wei, Qinghui; Chen, Yang; de Almeida, Amaury A.; Andreazza, Carmen M. [UNESP]; Yan, Bing (EDP Sciences, 2025)
We estimated radiative association rate coefficients for P( 4 S) atoms and P + ( 3 P) ions interacting with P( 4 S) and N( 4 S) atoms to form P 2 + and PN + cations, respectively. The required potential energy curves of P 2 + and PN + and the transition dipole moments coupling the states of interest were obtained using the multi-reference configuration interaction approach with a Davidson correction (MRCI+Q). The rate coefficients were obtained from the cross-sections, which were computed using a quantum mechanical method. The maximum rate constant values we predict are 3.13×10 −19 cm 3 s −1 at 10 K for the PN + cation and 1.66×10 −16 cm 3 s −1 at 3500→6000 K for the P 2 + cation. For the convenience of astrochemical applications, the thermal rate constants were fitted to the standard equation, k(T) = A ( T /300) α e β/T .